CEO letters: Hospitality corporate narratives during the COVID-19 pandemic - Im, Jinyoung (Int J Hosp Manag, 2021)
For hospitality organizations, the need for compelling corporate narratives is particularly acute in dealing with the COVID-19 crisis due to the scope and severity of its threat to employees, customers, the general public, and the fundamental survival of the company itself. Thus, this study aims to identify corporate narrative strategies and examine how hospitality companies deploy such narrative strategies with impression management tactics during the COVID-19 pandemic. Anchored in the Aristotelian concept of persuasive rhetoric and impression management theory, this study content-analyzed 57 CEO letters published by hospitality companies during the COVID-19 outbreak and found the prevalent rhetoric appeals and patterns of rhetoric appeals with impression management tactics embedded in the letters.